2016
DOI: 10.1021/acs.jpcc.6b06385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles on the Photophysics of Riboflavin: Consequences on the ROS Generation

Abstract: Fluorescence lifetimes of Rf in the absence and presence of Pec.AgNP (Table S1)…………………………………….S3Emission spectra of Rf in the absence and presence of Pec.AgNP (Figure S2)…………………………………………….S4 Calculation of the diffusion-controlled rate constant with the Smoluchowski equation……………………………….S5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…This result is in line with the increase of O 2 ( 1 Δ g ) yield produced by Rf in the presence of Pec@AgNP, which was previously demonstrated in time‐resolved phosphorescence experiments. According to the phosphorescence assays, a larger increment in rate of oxygen uptake is expected for concentrations of Pec@AgNP higher than those employed in the present work .…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…This result is in line with the increase of O 2 ( 1 Δ g ) yield produced by Rf in the presence of Pec@AgNP, which was previously demonstrated in time‐resolved phosphorescence experiments. According to the phosphorescence assays, a larger increment in rate of oxygen uptake is expected for concentrations of Pec@AgNP higher than those employed in the present work .…”
Section: Resultsmentioning
confidence: 61%
“…In this paper, we proved that incubation of HeLa cells with normal cell medium containing additionally Rf and Pec@AgNP lead to the incorporation of both the dye and the nanomaterial. We have previously demonstrated that a 1:1 complex (Rf‐Pec@AgNP) between Rf and Pec@AgNP is formed . While it is not possible for us to determine directly, that is, by spectroscopic means, whether and to which extent the complex exists, when incorporated into the cells, we have here given evidence for the synergistic photodamage effect by the nanoparticles and Rf (see Figs.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations